Mechanical inclusions identification by evolutionary computation - Schoenauer, Marc; Kallel, Leila; Jouve, Fran~ois (European Journal of Computational Mechanics, 1996)
The problem of the identification of mechanical inclusion is theoritically ill-posed, and to-date numerical algorithms have demonstrated to be inaccurate and unstable. On the other hand, Evolutionary Algorithms provide a general approach to inverse problem solving. However, great care must be taken during the implementation : the choice of the representation, which determines the search space, is critical. Three representations are presented and discussed. Whereas the straightforward mesh-dependent representation suffers strong limitations, both mesh-independent representation provide outstanding results on simple instances of the identification problem, including experimental robustness in presence of noise.